Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas V UPTD SD Negeri 80 Parepare - Musfirah, Musfirah; Amran, Muhammad; Rusdi, Wafiq Azizah (Universitas Negeri Makassar, 2024)
The problem in this study is that the learning outcomes of the fifth-grade students at UPTD SD Negeri 80 Parepare still need to meet the established Learning Goal Achievement Criteria (KKTP). This research aims to determine the improvement in student's learning process and outcomes by implementing the Problem-Based Learning (PBL) model. This study uses a qualitative approach with Classroom Action Research (CAR) type. The data collection techniques used are observation, tests, and documentation, while the data analysis techniques used are data condensation, data presentation, and drawing conclusions. The research was conducted in two cycles, each consisting of two meetings. In the first cycle, the research results on the learning process from the aspects of teachers and students reached the Sufficient (C) category, while the students' learning outcomes reached the Poor (K) category. In the second cycle, the research results on the learning process from the aspects of teachers and students and the students learning outcomes reached the Good (B) category. This study concludes that implementing the Problem-Based Learning (PBL) learning model can improve the learning process and outcomes in Science for fifth-grade students at UPTD SD Negeri 80 Parepare.